Convergent close-coupling method for positron scattering from noble gases - Fursa, Dmitry; Bray, Igor (Institute of Physics Publishing Ltd, 2012)
We present the convergent close-coupling formulation for positron scattering from noble gases (Ne, Ar, Kr and Xe) within the single-center approximation. Target functions are described in a model of six p-electrons above an inert Hartree–Fock core with only one-electron excitations from the outer p6 shell allowed. Target states have been obtained using a Sturmian (Laguerre) basis in order to model coupling to ionization and positronium (Ps) formation channels. Such an approach is unable to yield explicit Ps-formation cross sections, but is valid below this threshold and above the ionization threshold. The present calculations are found to show good agreement with recent measurements.